Malaria, helminths and malnutrition: A cross-sectional survey of school children in the South-Tongu district of Ghana - Ayeh-Kumi, P.F.; Addo-Osafo, K.; Attah, S.K.; Tetteh-Quarcoo, P.B.; Obeng-Nkrumah, N.; Awuah-Mensah, G.; Abbey, H.N.A.; Forson, A.; Cham, M.; Asare, L.; Duedu, K.O.; Asmah, R.H. (BioMed Central Ltd., 2016)
Background: As part of malaria characterization study in the South-Tongu district of Ghana, the current study was conducted to explore relationships between malaria, schistosomiasis, soil transmitted helminths and malnutrition in riparian community settings that had hitherto encountered episodes of mass deworming exercises. Methods: School-age children were enrolled in a cross-sectional study from April through July 2012. Stool and urine samples were examined respectively for helminths and Schistosoma haematobium. Blood samples were analyzed for malaria parasites and haemoglobin (Hb) concentrations, respectively. Anthropometric indices were measured. Relationships were determined using generalized linear models. Results: The results show low numbers of asymptomatic Plasmodium falciparum (9.2 %, n = 37/404) and S. haematobium (2.5 %, n = 10/404) infections. The associations between significance terms in the multivariate analysis for P. falciparum infections were further assessed to test the significance of the product terms directly i.e., age in years [adjusted odds ratio (AOR), 3.1; 95 % confidence interval (CI) 1.1-5.6], Hb concentration (AOR = 0.71; 95 % CI 0.42-2.3), and stunted malnutrition (AOR, 8.72; 95 % CI 4.8-25.1). The P. falciparum-associated decrease in mean Hb concentration was 2.82 g/dl (95 % CI 1.63-4.1 g/dl; P = 0.001) in stunted children, and 0.75 g/dl (95 % CI 1.59-0.085 g/dl; P = 0.076) in the non-stunted cohort. The anaemia-associated decrease in mean parasitaemia in stunted children was 3500 parasites/μl of blood (95 % CI 262.46-6737.54 parasites/μl of blood; P = 0.036), and in non-stunted children 2127 parasites/μl of blood (95 % CI -0.27 to 4.53; P = 0.085). Stunted malnutrition was the strongest predictor of S. haematobium infection (AOR = 11; 95 % CI 3.1-33.6) but significant associations as described for P. falciparum infections were absent. The population attributable risk of anaemia due to P. falciparum was 6.3 % (95 % CI 2.5-9.3), 0.9 % (95 % CI 0.4-2.3) for S. haematobium, and 12.5 % (95 % CI 9.11-19.52) for stunted malnutrition. Conclusion: Plasmodium falciparum, S. haematobium, intestinal helminths and their co-infections were uncommon in our school-age children. Stunting exacerbated the extent to which malaria was associated with loss in Hb concentration.
Keywords: Children; Ghana; Haemoglobin; Malaria; Malnutrition